(untitled) (Comillas Journal of International Relations, 2023)
Chipko is a movement made up mainly of rural women that originated in India, in the State of Uttar Pradesh, in the 1970s. It has been characterized for pursuing social and environmental goals based on non-violent resistance. However, it is a matter of debate whether Chipko fits within feminism and environmentalism. It is argued that its main influences are really Hinduism and India’s own culture, and that, in its origin, Chipko’s initial claim was only for the survival of rural communities. However, over time, Chipko has consolidated itself as a movement and its foundations and experiences have had great influence in other social movements both in Indi and beyond. Therefore, in this paper, we argue that to fully understand Chipko, it should be analyzed from a different perspective: ecofeminism. This article aims to demonstrate that Chipko should be considered an ecofeminist movement and that its non-violent methods have been a source of inspiration for other social causes and grassroots movements. We conclude the paper, reflecting on the need to de-Westernize concepts like feminism and environmentalism to better understand their continuous relevance and influence today.